Evaluating dental students’ satisfaction in clinical Periodontics courses at KSAU-HS: a cross-sectional study - Jawaher Abu Wathlan; Hussam Alqahtani (BMC Medical Education)
Abstract Background The National Commission for Academic Accreditation and Assessment (NCAAA) in Saudi Arabia underscores the importance of assessing student satisfaction to ensure program quality. No previous studies have explored the satisfaction levels of dental students enrolled in clinical Periodontics courses at King Saud Bin Abdulaziz University for Health Sciences (KSAU-HS). This study aims to assess dental students’ satisfaction with clinical Periodontics courses and to explore potential differences in satisfaction based on gender and academic level. Methods This cross-sectional study surveyed dental students enrolled in Periodontics courses at KSAU-HS during the 2022–2023 academic year. A web-based questionnaire was distributed via email. The survey covered six categories: learning objectives, course materials, content relevance, instructor knowledge, delivery style, and facility environment. Responses were analyzed using chi-square tests for gender differences and t-tests to compare satisfaction between third- and fourth-year students. Results The study included a balanced distribution of male (47.92%) and female (52.08%) participants, with 68.75% in their third year and 31.25% in their fourth year. Overall, students reported high satisfaction, with over 90% agreeing they understood the learning objectives and felt confident in applying their knowledge. No significant differences were found between male and female students (mean scores: 95.49 vs. 95.48) or between third- and fourth-year students (mean scores: 95.56 vs. 95.31), indicating consistent satisfaction across these groups. Conclusion High levels of satisfaction with clinical Periodontics courses at KSAU-HS suggest effective course design, clear objectives, and relevant content. The lack of significant associations with gender or academic level implies a uniformly positive educational experience. These findings underscore the importance of aligning course design with best practices in dental education to ensure graduates are well-prepared for clinical practice on a global scale.